Инженерно-физический факультет НТУ "ХПИ": достижения и перспективы - Конкин, Валерий Николаевич; Назаренко, Сергей Александрович (My University, 2017)
Рассмотрены основные этапы развития Инженерно-физического факультета НТУ "ХПИ". Сделан краткий обзор деятельности научно-педагогических школ. Приведена информация о кафедрах, специальностях специализациях факультета.

The history of Department for Engineering Physics became an integral part of the scientific technical, intellectual and cultural development of Ukraine. The name of Noble Prize winner L. D. Landau and the names of the world-known scientists such as academician A. K. Valter, S. P. Tymoshenko, K. D. Sinelnikov, V. A. Steklov, A. P. Philipov, A. M. Pidgornyi and many other names are connected with the Department of NTU "KhPI". The origination of the Ukrainian technical science in the field of Mechanics, Theory of Reliability is connected with the Department. The fundamental scientific trends were discovered and explored here. The Department for Engineering Physics trains specialists on 2 qualification levels. The first level is a 4-year training for Bachelor's degree, the second is a six years training to get a Master's degree. The Department trains full-time specialists in 5 specialties: information technologies, mechanics, applied mathematics, computer sciences. The University has a Student Palace with dancing hall, exhibition and conference halls, the Sports Center with 2 swimming pools, sport and recreation camp.
Distinguished achievements of the scientists and graduates of department for engineering physics
Keywords: инженерно-физический факультет; информационные технологии; компьютерная механика; виртуальное моделирование; НТУ "ХПИ"; Национальный технический университет "Харьковский политехнический институт"; высшее техническое образование; information technologies; mechanics; applied mathematics; computer sciences; scientists; Department for Engineering Physics; NTU "KhPI"